Unraveling the intricacies: understanding the complexities of obesity, body image, and demographic influences among Indonesian high school adolescents - Wiradinata, Harsono (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2025)
This research addresses Indonesia's significant obesity issue among teenagers, highlighted by the 2022 Indonesian Health Survey. It explores the correlation between overweight-obesity prevalence and body image disturbances in high school adolescents, with a sample of 185 individuals selected through random sampling. Inclusion criteria involve parental consent for overweight-obese adolescents, while exclusion criteria consider specific health conditions or unwillingness to participate. Ethically, respondent anonymity and the lack of biological materials alleviate concerns. BSQ-34 prevalence rate analysis reveals a complex landscape influencing body image disturbances. While age and gender show limited associations, Body Mass Index correlates significantly, emphasizing its role. Conversely, no notable correlation is found with bullying, parenting styles, and social comparison, highlighting the independence of body image disturbances. Media influence stands out, warranting comprehensive investigations. In conclusion, these findings stress the complexity of body image concerns, advocating for holistic comprehension and interventions beyond singular influences, emphasizing the multifaceted nature of factors affecting high school adolescents' body image perceptions.